Performance study of intra-domain mobility management - Rusli, Nazreen; Hassan Abdalla Hashim, Aisha; Ridzuan, Fauzana (2005)
Mobile IPv6 (MIPv6) describes how mobile node can change its point of attachment from one access router to another. Hierarchical Mobile IPv6 (HMIPv6) is the proposed enhancement for Mobile IPv6 that is designed to reduce the amount of signaling required and to improve handover speed for mobile connections. This is achieved by introducing a new network entity called Mobility Anchor Point (MAP). The former protocol deals within an inter-domain architecture and the latter in an intradomain system. This study makes a comparison between these protocols. The architecture and operation of each protocol is studied and they are evaluated based on the QoS parameters such as, packet loss, throughput and signaling overhead. The simulation was carried out using the Network Simulator-2. The outcome from these results has been discussed.